Hukm Shar`i and the reciprocal identification between its definition and subject matter: the missing link - Elgasim, Saad Abu; Ansari, Abdul Haseeb; Arifin, Mahamad (ISTAC, 2015)

(untitled)
When the nature of a particular notion is sought to be- known, one often resorts to look for its definition, and that definition, by its nature, often identifies the subject matter. Conversely, the definition sought for identifying the subject matter could not have been articulated before investigating the nature of the notion and designating its subject matter. This logical link of reciprocal identification between the definition of hukm and its subject matter is assumed missing. In order for it to be recovered, this paper investigates the nature of hukm shar7from both the perspective of its definition and that of its subject matter; Front both perspectives, that is, that of the definition of hukm and its subject matter, the nature of ltukm will be investigated through the presentation of the different views of the subject matter of dispute. This is to be followed by a critical analysis of that which searches for the truly distinctive character that provides the subject matter of dispute With its significance so that it can be used in selecting the appropriate view of the disputing views or, if not„ searching for it elsewhere. The distinctive character of bukin is thought to be embedded in legitimacy to which bindingness is tied, and therefore the definition suggested by theologians which identifies hukm with the communication of the hulas-give• is thought to be the appropriate definition.